PENGARUH PANJANG AXIS EMBRIO DAN LAMA PENYIMPANAN TERHADAP PERKECAMBAHAN BIBIT AREN - Idham Idham (Universitas Tadulako, 2011)
This study aimed to determine the influence of embryonic axis length and the storageduration on palm seed germination. The study was conducted at the laboratory of SeedScience and Technology, and the green house of Agriculture faculty-UNTAD from April toNovember 2008. A randomized block design with two factors was used. The first factorwas the axis length of embryo consisted of three levels (<2 cm, P1); 2-4 cm, P2; and >4 cm,P3). The second factor was the storage duration (10 days, L1; 20 days, L2; and 30 days, L3).All treatment combinations were replicated 3 times. The variables observed were: axislength of the embryo, seedling height, number of leaves, stems diameter, root length, dryweight of root, dry weight of shoot, and hypothetic index of vigor. The results showed thatthe axis length 2-4 cm of embryos stored for 20 days (L2P2) resulting in the best responseon germination of palm seeds compared to other treatmentsKey words: Stored duration, sugar palm, the axis lenght of the embryo.